Innate IL‐23/Type 17 immune responses mediate the effect of the 17q21 locus on childhood asthma. Issue 7 (29th May 2021) - Wang, Ni; Brix, Susanne; Larsen, Jeppe M.; Thysen, Anna H.; Rasmussen, Morten A.; Workman, Christopher T.; Stokholm, Jakob; Bønnelykke, Klaus; Bisgaard, Hans; Chawes, Bo L.
Abstract: Background: Several childhood asthma risk loci that relate to immune function have been identified by genome‐wide association studies (GWAS), but the underlying mechanisms remain unknown. Objective: Here, we examined whether perturbed innate immune responses mediate the association between known genetic risk variants and development of childhood asthma. Methods: Peripheral blood mononuclear cells from 336 six‐month‐old infants from the Copenhagen Prospective Studies on Asthma in Childhood (COPSAC2000 ) cohort were stimulated in vitro with six different innate ligands (LPS, CpG, poly(I:C), R848, HDMAPP and aluminium hydroxide together with low levels of LPS) followed by quantification of 18 released cytokines and chemokines 40 h after the stimulations. The innate immune response profiles were decomposed by principal component (PC) analysis, and PC1‐5 were used in mediation analyses of the effect of 25 known genetic risk variants on childhood asthma until age 7. Results: The effects of two variants from the 17q21 locus (rs7216389, rs2305480) on asthma and exacerbation risk were significantly mediated by immune parameters induced in response to ligands mimicking intracellular colonization; bacterial DNA (CpG) and double‐stranded viral RNA (poly(I:C)). The Th17 and innate lymphoid cell type 3‐amplifying cytokine IL‐23 was the most prominent cytokine involved. Conclusion: The 17q21 effect on childhood asthma and exacerbations was partly mediated by deregulation of IL‐23 in response to intracellular microbial ligands, which may suggest ineffective clearance of intracellular pathogens in the lungs. Abstract : In this study, we examined whether the effect of known childhood asthma genetic risk loci is caused by perturbed innate immune responses in infancy. The effects of two variants in the 17q21 locus on asthma and exacerbations until age 7 years were significantly mediated by immune mediators induced in response to ligands mimicking intracellular colonization, that is bacterial DNA (CpG) and double‐stranded viral RNA (poly(I:C)). The Th17 and innate lymphoid cell type 3‐amplifying cytokine IL‐23 was the most prominent cytokine involved. ​